Undercurrents: Queer Culture and Postcolonial Hong Kong - Hok-Sze Leung, Helen (UBC Press, 2009)
Undercurrents engages the critical rubric of "queer" to examine Hong Kong's screen and media culture during the transitional and immediate postcolonial period. Helen Hok-Sze Leung draws on theoretical insights from a range of disciplines to reveal parallels between the crisis and uncertainty of the territory's postcolonial transition and the queer aspects of its cultural productions. Leung explores Hong Kong cultural productions – cinema, fiction, popular music and subcultural projects – and argues that while there is no overt consolidation of gay and lesbian identities in Hong Kong culture, undercurrents of diverse and complex expressions of gender and sexual variance are widely in evidence. Undercurrents uncovers a queer media culture that has been largely overloo... Source: Publisher
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); _Nettoyé

“Citizen Journalism” in the Syrian Uprising: Problematizing Western Narratives in a Local Context - Al-Ghazzi, Omar (Communication Theory, 2014)
This article analyzes the term ‘citizen journalism’ against the backdrop of the Arab uprisings in order to show how it overlooks the local context of digital media practices. The first part examines videos emanating from Syria to illustrate how they blur the lines between acts of witnessing, reporting, and lobbying, as well as between professional and amateur productions, and civic and violent intentions. The second part highlights the genealogies of citizenship and journalism in an Arab context and cautions against assumptions about their universality. The article argues that the oscillation of Western narratives between hopes about digital media's role in democratization in the Arab World and fears about their use in terrorism circumscribe the theorization of digital media practices.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/comt.12047
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

Queer Korean Cinema, National Others, and Making of Queer Space in Stateless Things - Kim, Ungsan (Journal of Japanese & Korean Cinema, 2017)
Analyses the narrative and formal elements of Kim Kyung-mook's "Stateless things" (2011) to argue how it critiques South Korea’s ethnocentrism and homophobic social structures by delineating a queer use of space. Gives recent examples of homoeroticism in commercial and independent South Korean cinema. Argues that Kim's film expand the definition of queer Korean cinema by deconstructing and reconstructing the heteronormative, progress-driven cityscape of Seoul.
Num Pages: 61-79
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Asie (corpus analysé); 5-Identités diasporiques; _Nettoyé

‘Shanghai is burning’: Extravaganza, Transgender Representation and Transnational Cinema - Bao, Hongwei (Global Media and China, 2018)
This article offers a critical analysis of Matthew Baren’s 2018 film Extravaganza, a documentary about drag scenes in Shanghai. By focusing on some drag performers represented in this film, in tandem with an examination of the social and industry contexts of the film, as well as my interviews with the filmmaker and performers, I problematise the gender identity of the performers and the national identity of the film. Drawing on Deleuze and Guattari’s notion of ‘becoming’ and Song Hwee Lim’s discussion of ‘trans’, I propose to think about certain modes of transnational production with the critical concept of ‘becoming trans’. ‘Becoming trans’ offers a productive way of conceptualising new modes of ‘minor’ transnational cinematic connections in a globalised world without having to resort to identity politics.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

The Wonderful World of Queer Cinephilia - Ghosh, Shohini (BioScope: South Asian Screen Studies, 2010)
The silence around queerness is decisively broken. Much has happened in the last two decades. Today, there are queer groups, writers, activists, academics, filmmakers, and an increasing number of spaces where friendship, solidarity, and political engagement can be nurtured. Queer activism has been responsible for bringing a legal challenge to Section 377 (IPC) that criminalizes “sexual acts against the order of nature”.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Asie (corpus analysé); 5-Créateur.rice LGBTQ+; _Nettoyé

The Other in South Asian Religion, Literature and Film: Perspectives on Otherism and Otherness - Dimitrova, Diana (Routledge, 2013)
This book introduces the term "otherism" and looks at the discourse of otherism and the issue of otherness in South Asian religion, literature and film. It examines cultural questions related to the human condition of being the "other," of the process of "othering" and of the representation of "otherness" and its religious, cultural and ideological implications. The book applies the perspectives of ideological criticism, theories of hybridity, orientalism, nationalism, and gender and queer studies to gain new insights into the literature, film and culture of South Asia. It looks at the different ways of interpreting "otherness" today. The book goes on to analyze the ideological implications of the creation of "otherness" with regard to religious and cultural identity and the legitimation of power, as well as how the representation of "otherness" reflects the power structures of contemporary societies in South Asia. Offering a well-thought-out reflection on important cultural questions as well as a deep insight into the study of religion and "otherness" in South Asian literature and film, this book is a pioneering project that is of interest to scholars of South Asian Studies and South Asian religions, literatures and cultures.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

The Kids Are Not All Right: The Curious Case of Sapphic Censorship in City-State Singapore - Chen, Loretta (Queer Singapore : Illiberal Citizenship and Mediated Cultures, 2012)
The writer examines Singapore's Media Development Authority's censorship of representations of lesbianism in film, music video, television and theatre. She highlights the government surveillance and repression of portrayals of LGBT cultures and communities in Singapore by unpacking the ambiguities and contradictions underlying the censorship of these popular media forms. This reflects an institutional ‘inability to read lesbians’.
Keywords: 1-Cinéma; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); _Nettoyé

Filming Power and the Powerless: Zhao Liang’s Crime and Punishment (2007) and Petition (2009) - Li, Jie (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
This article discusses two recent works by emerging documentary auteur Zhao Liang, Crime and Punishment(2007) and Petition(2009). These penetrating observations of state-society relations in contemporary China render visible those who are un(der)represented, critique the deception of mass media images, and show the various complex ways in which power is connected to surveillance and visibility. Thus the filmmaker, his camera, and the spectators are implicated in power relationships as we cast voyeuristic, panoptic, activist, empathetic, or critical gazes upon the representatives of state power and upon the disenfranchised.
Keywords: 1-Cinéma; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Marking the Body: The Axiographics of the Visible Hidden Camera - Nornes, Abé Mark (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
This chapter contemplates the ethical dimensions of the specific brand of observational cinema found in China. Because there is no popular understanding of independent documentary—and also because filmmakers almost invariably use amateur video cameras and shoot alone—many subjects are oblivious to the fact that their images are being captured for films being screened around the world. It is in this sense that, while their cameras are perfectly visible, they are also hidden. This enables directors to capture “life unawares,” as if people were being shot by a hidden camera. In this context, directors make the films they want, ignoring the ethical implications of shooting people without being upfront about their intentions or asking for consent. The chapter closely examines a set of films to explore the axiographics of the documentary, in other words how ethics is rendered in the time and space of the moving image.
Keywords: 1-Cinéma; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

“To Whom Do Our Bodies Belong?”: Being Queer in Chinese DV Documentary - Robinson, Luke (DV-made China : digital subjects and social transformations after independent film, 2015)
In 1990s post-Reform China, a growing number of people armed with video cameras poured out upon the Chinese landscape to both observe and contribute to the social changes then underway. This digital turn has given us a 'DV China' that includes film and media communities across different social strata and disenfranchised groups. This study takes stock of these phenomena by surveying the social and cultural landscape of grassroots and alternative cinema practices.
Keywords: 1-Cinéma; 2-Étude de la réception; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

The Spectacular Crowd: Representing the Masses in DV Documentary - Shen, Shuang (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
In their introduction to a collaborative study of crowds organized by the Stanford Humanities Lab in 2000, Jeffrey T. Schnapp and Matthew Tiews observe that while the first half of the twentieth century witnessed a rise of collective social action and various forms of mass assembly, the second half was a period of the decline of collective political formations and the replacement by virtual and media-based assemblies for physical crowds (Schnapp and Tiews 2006, xi). The postindustrial political economy in the West is “characterized by the coexistence of media aggregation and bodily disaggregation,” Schnapp and Tiews claim (xi).
Keywords: 1-Cinéma; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des représentations; 3-Asie (corpus analysé); _Nettoyé

The Cruelty of the Social: Xianchang, Intersubjectivity, and Interobjectivity - Sniadecki, J. P. (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
At the closing awards ceremony for the 7th Annual DOChina Festival held in May 2010 in Songzhuang—a gentrified artists’ village at the far eastern edge of the Beijing municipality—young animator, poet, and filmmaker Xue Jianqiang was recognized with an honorable mention for his haunting documentary Martian Syndrome. The award came with 2000 RMB, a Panasonic DV camera (the jury’s official comments noted that Xue lacked his own camcorder and had to borrow one to make his film), and the chance to speak before a gathering of who’s who in Chinese independent documentary filmmaking.
Keywords: 1-Cinéma; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des représentations; 3-Asie (corpus analysé); 5-Identités diasporiques; _Nettoyé

DV and the Animateur Cinema in China - Voci, Paola (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
Film scholarship on the movie-making, movie-viewing, and movie-circulating practices that have developed since the mid-1990s in China has appropriately emphasized the role played by the rise of digital video (DV) and its impact on independent and, in particular, documentary filmmaking. In this chapter, I want to explore one line of development in DV independent production that has received much less attention—what I call animateur cinema—which concerns short digital animations that are made by and/or circulated for online (or on-mobile) moviemakers/viewers. Fan-originated digital animation or egao animation can also be found online, but my focus is on animateur cinema
Keywords: 1-Cinéma; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

The Recalcitrance of Reality: Performances, Subjects, and Filmmakers in 24 City and Tape - Wang, Qi (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
Since its beginning in the early 1990s, independent Chinese documentary has steadily built a reputation with its unflinching presentation of the underbelly of China’s economic boom and social sea changes. Individuals and groups whose experiences register the drastic costs of this process have become the most natural and common subject matter of independent documentaries. From the struggling artists who were among the first to quit state employment and go independent in Bumming in Beijing (Wu Wenguang 1990) to the art-aspiring young migrants from the rural area in The Other Bank (Jiang Yue 1995), from the homeless youngsters in Along the
Keywords: 1-Cinéma; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 5-Identités diasporiques; _Nettoyé

Toward a Digital Political Mimesis: Aesthetic of Affect and Activist Video - Zhen, Zhang (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
In 1990s post-Reform China, a growing number of people armed with video cameras poured out upon the Chinese landscape to both observe and contribute to the social changes then underway. This digital turn has given us a 'DV China' that includes film and media communities across different social strata and disenfranchised groups. This study takes stock of these phenomena by surveying the social and cultural landscape of grassroots and alternative cinema practices
Keywords: 1-Cinéma; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); _Nettoyé

Crossing Cameras in China: Christian Aesthetics and Realized Fictions - Zito, Angela (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
The films of director Gan Xiao’er are the first narrative features to take up Chinese Christians in their everyday concerns. This chapter discusses a pair of his films, one a fiction feature, the other a documentary made about taking that feature on the road and showing it in churches. It is about filmmaking practice—and especially documentary—as social occasion, as the concatenation between people of self-reflective moments of cultural creativity and critique. By social occasion, I mean that Gan has documented in the second film the moments of self-conscious “participation” in the fiction feature and in the documentary itself.
Keywords: 1-Cinéma; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

New Queer Sinophone Cinema: Local Histories, Transnational Connections - Pecic, Zoran 1981- (Palgrave Macmillan, 2016)
This book looks closely at some of the most significant films within the field of queer Sinophone cinema. Examining queerness in films produced in the PRC, Taiwan and Hong Kong, the book merges the Sinophone with the queer, theorising both concepts as local and global, homebound as well as diasporic.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé